Evolution of an academic career: DML's influence. (1st December 2015) - Mandeville, Tom
Abstract : When I first met Don, I was already an established research fellow in regional economics. Don's subsequent influence directly helped me follow my dreams, passions and interests. Thus, my academic career grew, developed and transformed from regional economics, to information economics, and eventually to evolutionary economics. This reflection traces that evolving process, illustrating Don's influence throughout.